The role of surface coarsening and sintering during thermal decomposition of titanium hydride. (1st March 2019) - Ben David, Roey; Finkelstein, Yacov; Nativ-Roth, Einat; Danon, Albert; Cohen, Dror; Rabkin, Eugen
Abstract: Temperature programmed desorption - mass spectrometry was utilized to study the non-isothermal hydrogen desorption from as-received and pre-oxidized TiH2 powder samples. Above the temperature of 750 °C, hydrogen desorption from the thermally decomposed as-received powder is kinetically delayed compared to that from the pre-oxidized samples. The scanning electron microscopy observations suggest that the delay stems from simultaneous surface coarsening and particles sintering that occur predominantly in the as-received powder at lower temperatures. It is also suggested that the difference in morphology evolution of the as-received and pre-oxidized powders originates from the dependence of Ti diffusion on the concentration of oxygen dissolved in Ti, since the oxide layer itself was found to dissociate at lower temperatures (∼500 °C). Highlights: H2 desorption completion from as-received TiH2 is delayed compared to oxidized TiH2 . Surface coarsening and particles sintering inhibit hydrogen desorption. The surface oxide layer dissociates above ∼500 °C by oxygen diffusion into the bulk. High oxygen content inhibits diffusion and coarsening during dehydrogenation.